STRUCTURAL ANALYSIS OF BUILT-UP MEMBERS WITH ANGLES - Bernuzzi, Claudio (Journal of Applied Engineering Science, 2020)
Built-up steel members are frequently used in lifting equipment structures, owing to the very advantageous ratio between the high load carrying capacity and the quite limited self-weight. Important applications are for cranes, from the tower and port cranes to the stiffleg derricks for mining applications, that are the core of the present paper. Design is usually carried out by using commercial finite element analysis packages (FEAP) offering only beam formulations efficiently developed for bi-symmetric cross-section members. The important effects associated with the buckling interaction between axial force and bending moments as well as with the presence of warping torsion are currently neglected in the analysis design, also because not yet included in standard provisions. The paper is focused on built-up members for stiffleg derricks made by angles and in particular on the analysis phase. Key features of single angles are presented stressing out the importance of capturing the buckling loads for compression, bending and compression plus bending. Furthermore, an applicative part is proposed: two stiffleg derricks, differing only in panel geometry, have been studied, considering each of them in six geometrical configurations. Structural analyses have been carried out by using two FEAPs differing for the degree of refinement of the implemented beam formulations. The proposed research outcomes allow for a direct appraisal of the important influence of the effects that are currently neglected in routine design because of the absence in engineering offices of FEAPs offering beam formulations adequate for mono-symmetric cross-section members.